Synthesis of C-ring hydrogenated sinomenine cinnamate derivatives via Heck reactions. Issue 11 (November 2019) - Pan, Hongmei; Lu, Tong; Wu, Xuedan; Jiang, Chuan; Gu, Chengwen; Zhang, Kehua; Jin, Jie
The synthesis of C-ring hydrogenated sinomenine derivatives is accomplished from sinomenine by treatment with Zn-Hg/HCl, halogenation with NIS, and Heck reactions with various acrylates. A total of nine novel sinomenine cinnamate derivatives are obtained in 84%–93% yields. The structures of all the derivatives are characterized by 1 H NMR, 13 C NMR, and MS spectroscopy.